Pengaruh Kualitas Produk, Harga, dan Kualitas Pelayanan Terhadap Tingkat Kepuasan Konsumen Pengguna Shopee - Tabina, Athaya Zahara; Sarah, Siti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
In this modern era, shopping is one of the daily activities carried out by people to meet their needs. By utilizing current technological developments, activities such as shopping through online shops, online shopping can be done using smartphones by visiting marketplaces/other media that can be used as buying and selling transactions. Online buying and selling transactions can be called e-commerce. This study was conducted using a quantitative method with a verification approach. T-test results, the t-value of Product Quality is 2.459, the t-value of Price is 3.719 and the t-value of Service Quality is 5.455 greater than the t table of 1.661, and the significance value of each variable is less than 0.05. It can be concluded that Product Quality has a positive and significant effect on the Level of Consumer Satisfaction of Shopee Users partially, Price has a positive and significant effect on the Level of Consumer Satisfaction of Shopee Users partially, Service Quality has a positive and significant effect on the Level of Consumer Satisfaction of Shopee Users partially, Product Quality, Price and Service Quality have a positive and significant effect on the Level of Consumer Satisfaction of Shopee Users simultaneously.